Letter - Thompson, J.
029-0155-001 Telegraphic Address: "WHOLESALE MANCHESTER" Telephone: BLACKFRIARS 1212. Extension No. Please Address Your Reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C 6th and 7th editions; Western UNION 5 Letter; Bentley complete phrase; Bentley second phrase; A.1. Marconi, and private. Our Reference EXPORT/ST/MM/6809. Your reference HVT/EAB/703. Dept International. 5th May, 1937. The Trades Union Congress General Council, Transport House, Smith Square, LONDON SW.1. Dear Sirs, We are in receipt of your letter of yesterday's date together with cheque amounting to £2,277.3.5d. in settlement of goods shipped by s.s. BACKWORTH from Immingham to Bilbao for which we thank you. Our Bank will be sending official receipt forward to you under separate cover. We should like to express our appreciation for the opportunity you afforded us of fulfilling your order for foodstuffs for Spain, and if at any time in the future you again contemplate making purchases for shipment to any Spanish port, we should be very glad to submit quotations if you so desire. Thanking you in anticipation, we remain, Yours faithfully, J. Thompson Export Department. 292/946/29/155